Pendekatan Metode dan Teknik Diklat di Era Revolusi Industri 4.0 - Muhammad Shohibuddin; Heni Listiana (Journal of Management, Accounting, and Administration, 2024)
Education and training in the era of the industrial revolution 4.0 must be supported by approaches, methods and techniques that are appropriate and appropriate to the conditions of the training participants. The aim of this research is to provide views regarding approaches, methods and techniques that can be applied in carrying out education and training activities. This research uses a library research method with primary data sources, namely the concept of approach, methods and techniques for implementing training. Secondary data sources were obtained from literature, including relevant books, journals and websites. The results of this research are: approaches that can be applied in implementing training in the era of the industrial revolution, namely: Critical Event approach, cycle approach and systems approach, while several methods and techniques that can be applied in implementing training are: project-based learning, e-learning learning and blended learning, adaptive learning, mentoring and coaching learning, and competency-based learning